Systems-level analysis of the mitotic entry switch - Domingo Sananes, M; Maria Rosa Domingo Sananes (2012)
Entry into mitosis in eukaryotes depends on the activation of the Cyclin-dependent kinase 1 (Cdk1), which phosphorylates many mitotic protein substrates. Activation of Cdk1 requires formation of a complex with Cyclin B (CycB), which gradually rises in concentration during interphase. However, in most organisms Cdk1 activation is not gradual but switch-like, because phosphorylation of the Cdk1-CycB complex by the Wee1 kinase normally keeps Cdk1-CycB inactive during interphase. Mitotic entry is induced when rapid dephosphorylation of Cdk1-CycB by the Cdc25 phosphatase causes abrupt activation of Cdk1-CycB. Cdk1-CycB in turn phosphorylates both Wee1 and Cdc25 leading to Cdc25 activation and Wee1 inhibition. This regulation creates both a positive and a double-negative feedback loop in the system, which are thought to generate a sharp, bistable switch that controls mitotic entry. Bistability is known to require positive feedback and ultrasensitivity, however, how ultrasensitivity arises in the mitotic switch is subject to extensive research efforts both experimentally and theoretically. In this thesis I explore several possible sources of ultrasensitivity in the mitotic switch through mathematical modelling. Based on theoretical considerations and experimental evidence, I show that the existence of multiple positive feedback loops, multisite phosphorylation, and Cdk1-CycB-dependent regulation of Cdk1-counteracting phosphatase activity can all contribute to ultrasensitivity and bistability in the mitotic switch. I analyse models of the mitotic switch including these bistability-generating mechanisms, to simulate and explain experimental data and make testable predictions. I argue that it is unlikely that a single mechanism is responsible for ultrasensitivity in this system, and that bistability requires a combination of different sources, including the ones studied here and others such as enzyme saturation and sequestration effects. I also highlight the importance of network architecture and coherent regulation of opposing reactions in generating efficient biochemical switches. Finally, I draw on recent experimental evidence and ideas derived from this analysis to propose a revised network of the mitotic switch.